Analysis of Composite Plate Subjected to Impact Load Part I: Analytical Solution - K. Radi, Samera; A. Abdulla, Fadhel (Journal of Engineering and Sustainable Development, 2009)
Composite laminated plates are found in many types of structural and aeronautical weight sensitive applications, such as, ships, automobiles. This work includes developing the equations of motion of composite laminated plates to obtain deformations and stresses under impact loading.The Hertzian impact law is modeled to describe the contact force between the projectile and the laminated plates. Analytical solution using (Navier solution) and theories (First Order Shear Deformation Theory „FSDT‟ and Higher Order Shear Deformation Theory „HOST 5‟) is presented. The results show the parametric effect of number of layers, lamination angle, and orthotropy ratio on the behavior of the laminated plates